Políticas públicas para o ensino superior: estudo sobre o acesso e a permanência de cotistas e não cotistas na Universidade Federal do Tocantins sob a perspectiva do desenvolvimento seniano - SOUSA , Eliezilda Oliveira de (Universidade Federal do Tocantins, 2024)
In this work, we carried out a study on the quota policy promoted by Law 12.711 / 2012, in which we addressed some aspects about the access and permanence of quota holders served by the reservation of vacancies in this Law and of non-quota students, who entered the Federal University of Tocantins (UFT), at the campus of Araguaína and Palmas, between the years 2010 and 2019, in a development perspective from access to higher education. Thus, our general objective was to analyze and problematize the public policy of quotas, whose specific objectives were: to analyze how UFT implemented quotas, to understand the flow of students and to identify access and permanence in courses, to examine behavior of the performance coefficient in the courses considered to be of greater or lesser prestige, between quota and non-quota students, through a quantitative approach, based on the analysis of secondary data made available by the Dean of Undergraduate Studies, by the Dean of Student Affairs and data available on the UFT institutional website. Among the main results found, we point out that there was a greater insertion of browns, blacks, and those from public schools, especially in courses of greater competition such as Medicine, Law, Engineering and Veterinary Medicine, but with signs of possible segregation by sex in these courses; in most courses, both at the Campus de Araguaína and the Campus de Palmas, the statistical test did not show a significant difference between the income ratio of non-quota holders and quota holders; and, in relation to permanence, we noticed that student assistance policies, as well as monitoring, contributed positively, however, the dropout rates of non-quota students and quota students still need more attention, in a more striking way in relation to quota students. Thus, by way of conclusion, considering the perspective of Senian development, which guided our analyzes, we understand that the quotas promoted greater access of the lower classes to undergraduate courses at UFT, however, in relation to permanence, even though there are some actions aimed at this end and having been shown to be effective, they need to be complemented by the development of other practices and / or policies, such as pedagogical follow-up, qualification of the staff (Teachers and Technical-Administrative). However, considering that there are many factors that influence this process, which were not considered in this study due to the nature of the data worked here, we suggest that other more detailed studies, per course, will need to be carried out in order to arrive at a more accurate diagnosis. precise in order to enable the institution of more effective measures regarding access and permanence, especially those less favored whose development as freedom can be achieved through the completion of a higher education course at a public university, with quality teaching and based on fulfilling its social inclusion function, such as UFT.